Recurrence of solitary fibrous tumor of the pleura with hypoglycemia (Doege–Potter Syndrome): a case report description - Wang, Chuxu; Cao, Tingting; Hu, Guodong; Min, Bo; Hu, Haibo; Liu, Bing; Wang, Yaqin; Zuo, Xiaohua (Frontiers in Oncology, 2023)
Hypoglycemia has multiple causes, but the most common is a complication of insulin treatment. In addition to insulin therapy, tumors such as insulinomas of pancreatic origin and extrapancreatic tumors causing paraneoplastic syndromes should also be considered. Solitary fibrous tumors of the pleura (SFTP) is rare tumor, which when associated with hypoglycemia causes Doege-Potter syndrome. This article reports a case of a 69-year-old man with Doege-Potter syndrome and underwent the first surgical resection for SFTP. However, the tumor recurred 9 years later with hypoglycemic symptoms and implant metastasis. This recurrent tumor originated from the visceral pleura, was more aggressive and invaded the diaphragm and parietal pleura. After the second surgical removal of the tumor, the hypoglycemic symptoms disappeared.